2014
DOI: 10.1007/s10072-014-1871-9
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine alleviated cytokine synthesis and dopamine deficit and improved motor dysfunction in the mice model of Parkinson’s disease

Abstract: It was previously reported that cytokines and neurotoxins released from activated inflammatory cells induced the loss of projecting dopaminergic neurons in the substantia nigra, which triggered the pathogenesis of PD. The present study investigated the effect of treatment with tetramethylpyrazine (TMP) on the central cytokine synthesis, striatal dopamine content and glutamatergic transmission, and behavioral performance in the rotarod task in mice injected with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The results revealed that stimulation with 1 µg/ml LPS for 24 h significantly inhibited cell viability. Previous studies have demonstrated that TMP exerts anti-inflammatory effects on hepatic stellate cells, a mouse model of Parkinson's disease and myocardial cells (39)(40)(41). The present study demonstrated that inflammation levels induced by LPS were significantly reduced by TMP in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 68%
“…The results revealed that stimulation with 1 µg/ml LPS for 24 h significantly inhibited cell viability. Previous studies have demonstrated that TMP exerts anti-inflammatory effects on hepatic stellate cells, a mouse model of Parkinson's disease and myocardial cells (39)(40)(41). The present study demonstrated that inflammation levels induced by LPS were significantly reduced by TMP in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have evidenced that TMP has the pharmacological activity of anti-platelet aggregation and the physiological functions of softening the blood vessels, increasing coronary blood flow, improving microcirculation and scavenging free radicals [2][3][4][5]. It has been used in clinical applications as a medicinal agent with high security for more than 30 years, especially in the treatment of patients with cerebral ischemic diseases, because of its neuroprotective effects and global cerebral ischemia [6,7].…”
Section: Article; Pharmaceutical Biotechnologymentioning
confidence: 99%
“…However, it must be mentioned that we could not exclude downstream signaling pathway suppression, such as CaMKII. Previous studies have demonstrated that TMP could inhibit the activation of the calcium/calmodulin/calmodulin-dependent protein kinase (Ca2+/CaM/CaMKII) pathway [ 27 ]. TMP may suppress CaMKII to attenuate neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%